Joint responsibility and understanding of resilience from a DMO perspective – an analysis of different situations in Bavarian tourism destinations - Pechlaner, Harald; Zacher, D.; Eckert, C.; Petersik, L. (2018)
© 2018, International Tourism Studies Association. Purpose: The purpose of this paper is to discuss responsibility in tourism destinations. On the basis of a resilience approach, central aspects of leadership and of responsibility in destination networks are introduced and, a contribution to a conceptual analysis of the future viability of tourism destinations is made. This contributes to a better understanding of resilience from a destination management organization (DMO) perspective in the context of shared responsibility. Design/methodology/approach: To achieve this goal, a qualitative interview series was conducted with destination managers in urban and rural areas. The interviews were evaluated using the method of GABEK®, in order to reveal and visualize semantic relationships between the specific statements. This method allows the representation of linkages and relationships of keywords from interview transcripts in the form of network graphs. Findings: A major result is the existence of a network of leaders who take responsibility for tourism development within a tourism destination. Within this network, the destination manager once again plays a key role by developing and formulating visions, goals and strategies. In this context, the relevant employees of the DMO have an important role to play, since they are an important resource of tourism development due to their experience and competences. Originality/value: The paper contributes to a practical view on the development of visions and strategies. It analyzes challenges and possible ways to communicate with the required political and public actors of the destination as well as with the service providers to regard destination development as a collaborative task.